2022
DOI: 10.2147/idr.s359919
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Response and Safety of Inactivated COVID-19 Vaccines in Liver Transplant Recipients

Abstract: Purpose To evaluate the response and safety of an inactivated vaccine (Sinovac Life Sciences Co., Ltd., Beijing, China) for coronavirus disease 2019 (COVID-19) in liver transplant (LTx) recipients from China. Patients and Methods Thirty-five recipients post LTx from the First Affiliated Hospital of Zhejiang University School of Medicine who received inactivated vaccine from June to October 2021 were screened. Information regarding vaccine side effects and clinical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Prieto J. [ 31 ] investigated the protective effect of inactivated vaccines in 11 LT patients, Tu Z. H. [ 15 ] evaluated the safety of inactivated vaccines in 35 LT patients. Data on the safety and protection of inactivated vaccines in large-scale LT patients are not available, as yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prieto J. [ 31 ] investigated the protective effect of inactivated vaccines in 11 LT patients, Tu Z. H. [ 15 ] evaluated the safety of inactivated vaccines in 35 LT patients. Data on the safety and protection of inactivated vaccines in large-scale LT patients are not available, as yet.…”
Section: Discussionmentioning
confidence: 99%
“…Local and systemic AEs were mostly mild, with fatigue being the most frequently detected systemic AE. Previous studies reported that 27%−51% vaccinated LT patients had systemic AEs (mostly fatigue and headache) following two doses of vaccines [ 15 , 35 , 36 ]. Compared with liver cirrhosis and other chronic liver diseases [ 16 , 17 ], LT patients had a relatively higher proportion of systemic AEs, which might be due to their impaired immune systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a previous study has suggested that liver function indicators remain within normal after COVID-19 vaccination in liver transplant recipients, and incidences of compromised graft function, graft rejection, neurological conditions or severe allergic reaction are not likely to occur [ 22 ]. In their studies, Tu et al and Burra & Russo observed that immune response to the inactivated COVID-19 vaccine and mRNA SARS-CoV2 vaccine was generally low among liver transplant recipients [ 23 , 24 ], and shorter time post liver transplantation is a predictor of this [ 23 ]. However, COVID-19 vaccination is generally safe in liver transplant recipients [ 22 ].…”
Section: Main Textmentioning
confidence: 99%
“…Data on the humoral response rates in LTR to different platforms of SARS-CoV-2 ranged from 17% to 87% after two doses, being significantly lower than in the general population [ 3 , 4 ]. The reduced immune response was more frequent in patients who received mycophenolate mofetil (MMF), those with a shorter time to transplantation and in patients with older age or with renal impairment [ 3 , [5] , [6] , [7] , [8] , [9] , [10] , [11] ].…”
mentioning
confidence: 99%